nfxB as a Novel Target for Analysis of Mutation Spectra in Pseudomonas aeruginosa - Monti, Mariela R. (Public Library of Science, 2013)

(untitled)
nfxB encodes a negative regulator of the mexCD-oprJ genes for drug efflux in the opportunistic pathogen Pseudomonas aeruginosa. Inactivating mutations in this transcriptional regulator constitute one of the main mechanisms of resistance to ciprofloxacin (Cip(r)). In this work, we evaluated the use of nfxB/Cip(r) as a new test system to study mutation spectra in P. aeruginosa. The analysis of 240 mutations in nfxB occurring spontaneously in the wild-type and mutator backgrounds or induced by mutagens showed that nfxB/Cip(r) offers several advantages compared with other mutation detection systems. Identification of nfxB mutations was easy since the entire open reading frame and its promoter region were sequenced from the chromosome using a single primer. Mutations detected in nfxB included all transitions and transversions, 1-bp deletions and insertions, >1-bp deletions and duplications. The broad mutation spectrum observed in nfxB relies on the selection of loss-of-function changes, as we confirmed by generating a structural model of the NfxB repressor and evaluating the significance of each detected mutation. The mutation spectra characterized in the mutS, mutT, mutY and mutM mutator backgrounds or induced by the mutagenic agents 2-aminopurine, cisplatin and hydrogen peroxide were in agreement with their predicted mutational specificities. Additionally, this system allowed the analysis of sequence context effects since point mutations occurred at 85 different sites distributed over the entire nfxB. Significant hotspots and preferred sequence contexts were observed for spontaneous and mutagen-induced mutation spectra. Finally, we demonstrated the utility of a luminescence-based reporter for identification of nfxB mutants previous to sequencing analysis. Thus, the nfxB/Cip(r) system in combination with the luminescent reporter may be a valuable tool for studying mutational processes in Pseudomonas spp. wherein the genes encoding the NfxB repressor and the associated efflux pump are conserved.